Mobilising the periphery. Incubator for urban innovation. - (:unkn) unknown (My University, 2019)
Mobilising the periphery was a series of five symposia that took place at ANCB The Aedes Metropolitan Laboratory between June 2015 and April 2018. It was conceived in collaboration with the Schindler Transit Management Group to identify and understand the urban development patterns emerging in peripheries worldwide.
Keywords: Stadtentwicklung; Stadtwachstum; Stadtrand; Stadtrandgebiet; Stadtumland; Stadt-Umland-Beziehung; Peripherie; Stadtsoziologie; International; Sozialinnovation